Feed intake, digestibility, ruminal fermentation, growth performance, and carcass traits of lambs fed corn silage treated with Lentilactobacillus buchneri and stored for different times - Rossi, Luis G. [UNESP]; Rabelo, Carlos H.S.; Andrade, Marina E.B. [UNESP]; Siqueira, Gustavo R. [UNESP]; Vicente, Eduardo F. [UNESP]; Nogueira, Denismar A.; Reis, Ricardo A. [UNESP] (Elsevier, 2023)
Our objective was to investigate the impact of inoculation and storage length of flint corn silage on the metabolic and production responses of lambs. A flint corn hybrid was harvested with 315 g dry matter (DM)/kg and ensiled in concrete pipe silos without (control) or with Lentilactobacillus buchneri CNCM I-4323 at 1 × 105 cfu/g of fresh forage for 120, 240 and 360 d (n = 2 for each treatment). Such silages were used to formulate six different diets. Sixty non-castrated male Dorper × Santa Inês lambs were used in the feeding program (n = 10). Additionally, eight ruminally cannulated Dorper × Santa Inês crossbred lambs were used to measure the ruminal fermentation (n = 4). Extending the storage of corn silage from 120 to 360 d increased the contents of soluble protein (P = 0.030; 415–490 g/kg CP) and ammonia-N (P = 0.047; 82.5–114 g/kg total N). Compared to the control, inoculation resulted in higher (P < 0.05) concentration of lactic (+19.9 %) and acetic acid (+38.6 %), and lower butyric acid (–25.3 %), ammonia-N (–23.5 %), and DM loss (–36.2 %). The aerobic stability of corn silage was also improved by inoculation (P = 0.002; +160 h compared to the control). An interaction between storage length and inoculation was reported for feed intake, and lambs had increased DMI (P < 0.001) by feeding the inoculated silage stored for 120 d. Overall, the total-tract starch digestibility increased (P = 0.041) with longer storage (120 d = 94.4 %; 240 d = 95.7 %; 360 d = 96.5 %). However, the total VFA was unchanged (P > 0.05) while the ruminal molar proportion of propionate decreased from 22.8 to 20.7 mM/100 mM in lambs fed corn silage stored for 120 and 360 d (P = 0.004). Lengthening silage storage from 120 to 240 and 360 d tended (P = 0.06) to increase the ADG of lambs by 4.6 % and 10.2 %, respectively (120 d = 0.216 kg/d; 240 d = 0.226 kg/d; 360 d = 0.238 kg/d). Moreover, the feed efficiency was substantially improved (P = 0.008) by 5 % and 14 % when the silages were stored for 240 and 360 d compared to 120 d. In opposite, inoculation had no effect (P > 0.05) on ADG and feed efficiency of lambs. Final hot carcass weight (data ranged from 16.8 to 17.2 kg) and 12th rib longissimus muscle area (data ranged from 13.8 to 14.7 cm2) were not affected by treatments (P > 0.05). Overall, only few parameters of carcass and meat traits of lambs were altered by storage length and inoculation, but it were of minor biological importance. In conclusion, the productivity responses of lambs were enhanced by increasing the storage length of flint corn silage, but inoculation with L. buchneri did not contribute to improve animal performance.
Keywords: Animal performance; Flint corn silage; Lentilactobacillus buchneri; Ruminal fermentation; Starch digestion; Storage length